Critical evaluation and recalculation of current systematic reviews with meta-analysis on the effects of acute and chronic stretching on passive properties and passive peak torque - Warneke, K.; Lohmann, L. H.; Plöschberger, G.; Konrad, A. (European Journal of Applied Physiology, 2024)
Purpose Muscle, tendon, and muscle-tendon unit (MTU) stiffness as well as passive peak torque (PPT) or delayed stretching pain sensation are typical explanatory approaches for stretching adaptations. However, in literature, differences in the study inclusion, as well as applying meta-analytical models without accounting for intrastudy dependency of multiple and heteroscedasticity of data bias the current evidence. Furthermore, most of the recent analyses neglected to investigate PPT adaptations and further moderators.